2019
DOI: 10.3390/su11226498
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reflection and General Mental Ability as Predictors of Job Performance

Abstract: This paper presents a study with four independent samples on the validity of cognitive reflection (CR) for predicting job performance and academic outcomes. The results showed that CR was a valid predictor of academic outcomes (i.e., grades and exam marks) and job performance (i.e., assessment center ratings). The magnitude of the CR validity was similar to the validity of GMA. Moreover, we found that CR and GMA were moderately correlated, and multiple regression analyses showed that CR added a small amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 81 publications
(110 reference statements)
0
14
0
1
Order By: Relevance
“…This is also justified in the great amount of variance that both measures shared. Previous studies have shown that CRT-10 and CRT-3 are highly correlated [ 41 , 65 , 67 69 ]. For this sample, the theoretical correlation (observed correlation corrected by measurement error in both measures) between CRT-10 and CRT-3 was .81, indicating that both tests are assessing the same construct, and consequently, one can be substituted for the other.…”
Section: Discussionmentioning
confidence: 99%
“…This is also justified in the great amount of variance that both measures shared. Previous studies have shown that CRT-10 and CRT-3 are highly correlated [ 41 , 65 , 67 69 ]. For this sample, the theoretical correlation (observed correlation corrected by measurement error in both measures) between CRT-10 and CRT-3 was .81, indicating that both tests are assessing the same construct, and consequently, one can be substituted for the other.…”
Section: Discussionmentioning
confidence: 99%
“…This contribution goes beyond the physical environment, considering also the extent to which organizational practices promote workers' well-being [1]. A key process that helps organizations to be sustainable is personnel selection [2], which consists of incorporation, through a fair and transparent process, of workers who best fit the job. To do this, is necessary for the selection instruments to demonstrate their relationship with performance.…”
Section: Introductionmentioning
confidence: 99%
“…Job performance (JP) can be defined as the "total expected value to the organization of the discrete behavioral episodes that an individual carries out over a standard period of time" [88] (p. 39). The state-of-the-art research on JP research highlights a proliferation of theoretical and empirical studies on JP predictors, including: employees' ability, especially in entry-level jobs [89]; psychological well-being and job satisfaction [90]; employee engagement [91,92]; work stressors and coworker support [93]; ability and non-ability [94]; emotional and cognitive intelligence [95,96]; and cognitive reflection [97].…”
Section: Job Performancementioning
confidence: 99%